2021
DOI: 10.3390/ijms22041996
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Systematic Review of Human Knee Post-Traumatic Osteoarthritis (PTOA): Timeline of Clinical Presentation and Disease Markers, Comparison of Knee Joint PTOA Models and Early Disease Implications

Abstract: Understanding the causality of the post-traumatic osteoarthritis (PTOA) disease process of the knee joint is important for diagnosing early disease and developing new and effective preventions or treatments. The aim of this review was to provide detailed clinical data on inflammatory and other biomarkers obtained from patients after acute knee trauma in order to (i) present a timeline of events that occur in the acute, subacute, and chronic post-traumatic phases and in PTOA, and (ii) to identify key factors pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(94 citation statements)
references
References 276 publications
(579 reference statements)
3
83
0
8
Order By: Relevance
“…In summary, IL-1β is considered to mediate its effects on the actin cytoskeleton through the small GTPases RhoA and Rac1 [70,221], whereas IL-6 induces actin polymerization [222] and both IL-6 and IL-8 are thought to signal through the Rho-ROCK pathway [223] ( Figure 6). Additionally, the connection between multiple pro-inflammatory cytokines, specifically TNF-α and IL-6, with actin cytoskeleton remodeling and SF formation, might prove relevant in the context of post-traumatic AC degeneration and clinical disease because our recent evidence-based systematic review identified TNF-α and IL-6 as causal factors in inducing post-traumatic OA (PTOA) [224].…”
Section: Pro-inflammatory Cytokine Signaling Associated With the Chonmentioning
confidence: 99%
“…In summary, IL-1β is considered to mediate its effects on the actin cytoskeleton through the small GTPases RhoA and Rac1 [70,221], whereas IL-6 induces actin polymerization [222] and both IL-6 and IL-8 are thought to signal through the Rho-ROCK pathway [223] ( Figure 6). Additionally, the connection between multiple pro-inflammatory cytokines, specifically TNF-α and IL-6, with actin cytoskeleton remodeling and SF formation, might prove relevant in the context of post-traumatic AC degeneration and clinical disease because our recent evidence-based systematic review identified TNF-α and IL-6 as causal factors in inducing post-traumatic OA (PTOA) [224].…”
Section: Pro-inflammatory Cytokine Signaling Associated With the Chonmentioning
confidence: 99%
“…The global prevalence of knee OA is 16% in individuals aged 15 and over and 23% in individuals aged 40 and over [ 2 ]. Post-traumatic osteoarthritis (PTOA) is a major cause of early knee OA [ 3 ] with 22–50% of people developing clinical symptoms of PTOA [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ] within only a few years of an acute knee trauma [ 1 , 11 , 12 , 13 , 14 , 15 ] due to injuries such as intraarticular fracture, injury to the anterior cruciate ligament (ACL) alone or combined with medial collateral ligament or meniscus injuries [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. This, as of yet, incurable, multifactorial chronic disease consists of multiple co-pathologies of the articular cartilage, synovial fluid, synovial membranes, and bone.…”
Section: Introductionmentioning
confidence: 99%
“…This, as of yet, incurable, multifactorial chronic disease consists of multiple co-pathologies of the articular cartilage, synovial fluid, synovial membranes, and bone. Importantly, it is also connected with systemic manifestations of the disease, in which inflammation plays a key causal role in inducing knee PTOA disease progression [ 3 ]. This systemic response begins within 1 week of knee trauma, leading to higher than normal levels of inflammatory and injurious biomarkers present in the synovial fluid, blood and urine, and can persist for many years after knee injury ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations